Altered Expression of Complement Regulatory Proteins CD35, CD46, CD55, and CD59 on Leukocyte Subsets in Individuals Suffering From Coronary Artery Disease - Mishra, Nitesh; Mohata, Madhav; Narang, Rajeev; Lakshmy, R.; Hazarika, Anjali; Pandey, R. M.; Das, Nibhriti; Luthra, Kalpana (Frontiers in Immunology, 2019)
Studies conducted in animal models have suggested membrane complement regulatory proteins to play an important role in the pathophysiology of CAD. In this study, a total of 100 individuals with stable CAD and 100 healthy controls, both groups predominantly male, were recruited. We evaluated the plasma levels of complement regulatory proteins (Cregs) CD35, CD46, CD55 and CD59; their surface expression on granulocytes, lymphocytes, and monocytes by flow cytometry and their mRNA expression in total leukocytes by quantitative PCR. The soluble forms of Cregs, C3c, MASP-2, PAF-AH and inflammatory cytokines were quantified by ELISA. High plasma levels of C3c, indicative of complement activation along with significantly low levels of Cregs were observed in CAD patients. A significantly lower expression of CD46 and CD55 on the surface of lymphocytes, monocytes and granulocytes and higher surface expression of CD35 and CD59 on granulocytes (p < 0.0001) was seen in CAD patients compared to healthy donors. The high expression of CD59 on granulocytes positively correlated with severity of disease and may serve as a potential marker of disease progression in CAD.